Antimicrobial resistance trends in Escherichia coli, Klebsiella pneumoniae and Proteus mirabilis urinary isolates from Switzerland: retrospective analysis of data from a national surveillance network over an 8-year period (2009–2016) (Swiss Medical Weekly, 2019)
OBJECTIVES Most urinary tract infections (UTIs) are treated empirically with antibiotics, making comprehensive resistance surveillance data essential to guide empiric regimens. We describe trends in the antibiotic resistance of urinary Enterobacteriaceae isolates in Switzerland between 2009 and 2016. METHODS We analysed data from routinely collected Escherichia coli, Klebsiella pneumoniae and Proteus mirabilis urinary samples from community and hospital settings in Switzerland. The data were collected by ANRESIS, the national laboratory-based antimicrobial resistance surveillance system. Our analyses focused on resistance to antibiotics commonly prescribed for UTIs for the period 2009–2016. Only the first isolate per patient per year was included. RESULTS 297,200 urinary samples were included in the analysis, of which 246,656 (83.0%) were E. coli isolates. Overall, E. coli showed high susceptibility to 3rd/4th-generation cephalosporins, nitrofurantoin and fosfomycin, with the annual proportions of resistant isolates